Alagille Syndrome: A Focused Review on Clinical Features, Genetics, and Treatment - Kohut, Taisa J.; Gilbert, Melissa A.; Loomes, Kathleen M. (Seminars in Liver Disease, 2021)
Alagille syndrome (ALGS) is an autosomal dominant disorder caused by pathogenic variants in JAG1 or NOTCH2, which encode fundamental components of the Notch signaling pathway. Clinical features span multiple organ systems including hepatic, cardiac, vascular, renal, skeletal, craniofacial, and ocular, and occur with variable phenotypic penetrance. Genotype–phenotype correlation studies have not yet shown associations between mutation type and clinical manifestations or severity, and it has been hypothesized that modifier genes may modulate the effects of JAG1 and NOTCH2 pathogenic variants. Medical management is supportive, focusing on clinical manifestations of disease, with liver transplant indicated for severe pruritus, liver synthetic dysfunction, portal hypertension, bone fractures, and/or growth failure. New therapeutic approaches are under investigation, including ileal bile acid transporter (IBAT) inhibitors and other approaches that may involve targeted interventions to augment the Notch signaling pathway in involved tissues.
Keywords: JAG1; NOTCH2; cholestasis; liver transplant